A New Formula to Quantify the National Energy Security of the World's Top Ten Most Populous Nations - Nelwan, Adinda Franky; Dalimi, Rinaldy; Hudaya, Chairul (International Journal of Energy Economics and Policy, 2020)
Quantification of global sustainable energy security (ES) becomes urgent, but the concepts of ES are still not clear. Thus, this paper is originated from philosophical ES studies, in which the various concepts came from the differences in determining the observed multi-matters (energy, equipment, human, and ecosystem: EPME) and point of view to see the EPME. Therefore, this research is aimed at measuring the EPME variables, producing ES material quantities (Qes). Qes is derived after a 4-stage unification and is defined in a formula. The formula is then applied to calculate the top ten populous nations in the world from 1990 to 2015. Based on the top Qes values, the rankings are Russia (Fed.), USA, Japan, Brazil, China, Indonesia, India, Nigeria, Pakistan, and Bangladesh. The results also highlighted the Qes disparities between nations. A relationship between Qes and National Power Indicator (NPI) was also explored, indicating the ES saturation in the USA and Japan; and the macro energy-policy instability phenomenon in Nigeria. In addition, a comparison of Qes ranking to those of other scholars' results was presented. Finally, the macro sustainable energy policy implication is also highlighted. Keywords: National Energy Security, Quantification Formula, National Power, Sustainable Energy Policy JEL Classifications: A12, C43, Q43, Q48 DOI: https://doi.org/10.32479/ijeep.10245